Deformation Properties and Fatigue of Bituminous Mixtures - Frantisek Schlosser; Jan Mikolaj; Viera Zatkalikova; Juraj Sramek; Dominika Durekova; Lubos Remek (Advances in Materials Science and Engineering)
Deformation properties and fatigue performance are important characteristics of asphalt bound materials which are used for construction of pavement layers. Viscoelastic asphalt mixtures are better characterized via dynamic tests. This type of tests allows us to collate materials with regard to axle vibrations which lie usually in the range of 6 Hz–25 Hz for standard conditions. Asphalt modified for heat sensitivity in the range from −20°C to +60°C has significant impact on the overall characteristics of the mixture. Deformation properties are used as inputs for empirical mixture design, and fatigue performance of asphalt mixtures reflects the parameters of functional tests. Master curves convey properties of asphalt mixtures for various conditions and allow us to evaluate them without the need of time expensive testing.